(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Home loans play a major role in India to improve the standard of living, particularly forth economically weaker sections and the middle economic class society. Housing, being one of the basic needs for human, takes the major chunk of one’s income. Home loans came as a boon to people, who dreams of owing a house, even at the very early stage of one’s life. Home loan decisions are largely influenced by various factors including service quality, convenience, interest rates etc., With banks becoming more competitive and extending exclusive services for customers is the key to attract them, this paper analyses the determinants and the satisfaction level of home loan customers of SBI. Through a survey with a structured questionnaire, this project investigates the factors affecting their loan purchase decision based on various demographic factors. Ease in installments, monetary benefits, easy installments are the crucial factors in home loan decision making. At SBI, both have average rating due to more competition in the market. The paper also explains the customer satisfaction level and the willingness of customers to recommend SBI home loans to others. The study not only evaluates the various factors affecting customer preferences, but also provides insights in to enhancing customer experience to increase satisfaction and loyalty in this competitive banking industry.